Assessing impacts of public policies towards environmental sustainability in an EU region: North of Portugal - Medeiros, E.; Valente, B. (European Planning Studies, 2024)
Environmental sustainability has been a key policy goal of the European Union (EU), particularly under recent EU Cohesion Policy strategic frameworks. This paper contributes to the analysis of the relevance of EU Cohesion Policy-related environmental sustainability investments, by assessing the impacts of the Operational Programme for Sustainability and Use of Resources (POSEUR 2014–2020), in the Portuguese North NUTS II. In detail, the impact scores of the following five analytical dimensions related to this programme were obtained: (i) low-emissions economy, (ii) adaptation to climate change, (iii) risk prevention and management, (iv) environmental protection and (v) resource efficiency. The analysis was supported by a territorial impact assessment methodology (TARGET_TIA) which was complemented by an online analytic geographic information system (GIS) policy evaluation platform (Impact-WEB_GIS). The results showed that the POSEUR’s regional implementation efficiency fell short of the stakeholders’ expectations. This can be explained by factors such as the obstacles posed by the prior underdeveloped infrastructural conditions, coupled with the panorama created by the Covid-19 outbreak. Nonetheless, the risk prevention and management dimension had a solid positive impact score that reflected the efficacy of POSEUR in tackling environmental threats, mostly in rural ecosystems.